Power communication website bandwidth estimation method based on position weighting - Zhengjia ZHU; Xinyu YOU; Chenxi ZHENG; Li LI; Bing FAN (Dianxin kexue)
A power communication network site point communication bandwidth estimation method was proposed,which was related to the field of power communication networks.Firstly,according to a topology diagram of a power communication network,the local importance of the power communication site in the power communication network was determined.Then,the local importance and global importance of the power communication website was merged to obtain the actual importance value of the power communication website.Secondly,according to the actual importance value,each station’s communication bandwidth estimation model was determined.The data traffic redundancy factor was calculated based on the site communication bandwidth estimation model to calculate the planning bandwidth of the power communication site.The station’s position in the network topology was used to calculate the importance of the site and the importance of the node was introduced into the communication bandwidth of the site in the proposed method.In the estimation,the inaccuracy of traditional site communication bandwidth estimation result was overcome.